ICT Update 92: Reflections on digitalisation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2019)
In this issue, we reflect back on almost 20 years of ICTUpdate (nearly 100 issues). ICT Update’s objective has always been to capture contemporary developments in ICTs for agriculture; the trends, latest technologies and stories from the field. By looking back, we can see significant changes in the ICT4Ag landscape, and draw lessons on how to move forward and address ongoing challenges for inclusion, adoption and innovation. This issue highlights three of ICTUpdate’s recurring themes: learning; barriers for inclusion and adoption of ICTs; and innovation and entrepreneurship.